The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1029/2019jc015782
|View full text |Cite
|
Sign up to set email alerts
|

Modeled Impacts of Sea Ice Exchange Processes on Arctic Ocean Carbon Uptake and Acidification (1980–2015)

Abstract: A regional Arctic ice ocean model incorporating biogeochemical processes occurring inside the sea ice and water column is used to assess changes to the Arctic Ocean's carbon system, including oceanic carbon uptake and ocean acidification, over the recent period of Arctic sea ice decline (1980–2015). Two novel modifications are the following: (1) incorporation of carbon uptake by sea ice algae and (2) modification of the sea ice carbon pump to allow for vertical transport by brine plumes with high concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…To reduce the uncertainty rising from limited observations, great efforts have been made by the oceanographic community to extend the spatial and temporal coverage of p CO 2 on the Chukchi shelf. Approaches such as interpolation (Evans et al., 2015), ocean‐biogeochemistry coupled model (Manizza et al., 2019; Mortenson et al., 2020), and artificial neural network‐based self‐organizing map (SOM) technique (Laruelle et al., 2017; Roobaert et al., 2019; Yasunaka et al., 2016) have been proposed to create monthly or annual climatology of ∆ p CO 2 in western Arctic coastal ocean. These approaches provide general variability in biogeochemical characteristics within this broad and rapidly changing polar coastal ocean, however, their applicability in the Chukchi Sea may have limitations.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the uncertainty rising from limited observations, great efforts have been made by the oceanographic community to extend the spatial and temporal coverage of p CO 2 on the Chukchi shelf. Approaches such as interpolation (Evans et al., 2015), ocean‐biogeochemistry coupled model (Manizza et al., 2019; Mortenson et al., 2020), and artificial neural network‐based self‐organizing map (SOM) technique (Laruelle et al., 2017; Roobaert et al., 2019; Yasunaka et al., 2016) have been proposed to create monthly or annual climatology of ∆ p CO 2 in western Arctic coastal ocean. These approaches provide general variability in biogeochemical characteristics within this broad and rapidly changing polar coastal ocean, however, their applicability in the Chukchi Sea may have limitations.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to complex autonomous instruments, the distributed deployment of position-tracking buoys has provided information about the localized and aggregate ice dynamics, allowing relationships to the wind and ocean forcing to be identified. The corresponding time period, when the Central Observatory was unattended, was a critical time to complete our observations of the full seasonal cycle of the ice within the DN, including optical measurements of biology and chemistry, all subject to changing rapidly with climate change (Bluhm et al, 2020;Mortenson et al, 2020). Hence, there is a continuous need for more telemetered, autonomous observations, such as those of the DN.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the high solubility of CO 2 in low-temperature waters, the Arctic Ocean and its adjacent marginal seas serve as a significant CO 2 sink (Anderson and Kaltin, 2016;Yasunaka et al, 2018). Observations and model simulations have indicated that the Arctic Ocean absorbs 58-180 Tg C per year, accounting for 2%-7% of the global oceanic carbon sink (Manizza et al, 2013;Yasunaka et al, 2016;Mortenson et al, 2020). In recent decades, rapid and diverse changes, for example the increased seawater temperature, ice sheet melt, and an extended ice-free period, have occurred in Arctic ecosystems (Screen and Simmonds, 2010;Shepherd et al, 2012;Jeong et al, 2018).…”
Section: Introductionmentioning
confidence: 99%